FORMATION OF STUDENTS COMMUNICATIVE COMPETENCE IN RUSSIAN LANGUAGE LESSONS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the formation of communicative competence among university students in the process of learning the Russian language. The ability to communicate effectively in various contexts is a key goal in modern language education. In this regard, the development of communicative competence becomes a priority, especially in countries with multilingual and multicultural environments like Uzbekistan. The study examines the theoretical foundations of communicative competence, its structural components, and its relevance to the learning goals in higher education. Particular attention is given to the practical methods used to improve communicative skills, including interactive activities, dialogical speech training, and the integration of cultural content. Additionally, the article highlights how current pedagogical strategies, such as task-based learning and project-based learning, contribute to the development of speech fluency, confidence, and cross-cultural understanding. Emphasis is placed on classroom practices that foster student engagement, motivation, and real-world language use. This research also reviews contemporary literature, presents results of classroom experiments, and provides suggestions for educators seeking to enhance communicative competence in Russian language classes.